The contribution of women's employment and earnings to household income inequality: a cross-country analysis - Harkness, Susan (Luxembourg, 2010)
"Aggregate data shows an inverse relationship between female employment and income inequality. This paper investigates this relationship using micro-data for seventeen OECD countries. In all countries, female earnings exert an equalising force on the distribution of income in spite of large employment gaps between high and low educated women. There are marked similarities across countries; even in Nordic countries where employment rates are high female earnings comprise a small proportion of the family budget and single women, employed or not, are overrepresented in the bottom of the income distribution. The US is the one country that stands out, with greater earnings equality among couples and more single women households making it into the top quintile. For all countries, raising female employment and reducing employment inequality between women would have a substantial impact on reducing household income inequality, and a far larger impact than reducing the gender pay gap."